2017
DOI: 10.1016/j.jcyt.2017.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous infusion of adipose-derived stem/stromal cells improves functional recovery of rats with spinal cord injury

Abstract: Our findings indicated that intravenously transplanted ASCs gradually accumulated in the injured spinal cord, where cytokines such as CINC-1 activated ERK1/2 and Akt, leading to functional recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…Transplantation of various cells after SCI has led to increase in GDNF mRNA expression [58][59][60]. GDNF increases survival of motor and sensory neurons, improves motor function, induces neurogenesis and axonal growth, enhances myelination, and alleviates pain (analgesia effect) [35,[58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Transplantation of various cells after SCI has led to increase in GDNF mRNA expression [58][59][60]. GDNF increases survival of motor and sensory neurons, improves motor function, induces neurogenesis and axonal growth, enhances myelination, and alleviates pain (analgesia effect) [35,[58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…14,71 Functional experiments indicate that intravenous application of AD-MSCs improve hindlimb motor function through activation of angiogenesis along with upregulation of upstream kinase protein activity, such as ERK1/2 and Akt, in turn promoting cellular survival pathways and tissue-repair mechanisms. 42 However, while AD-MSC transplantation has been evaluated in animal SCI models, there remains a paucity of large, longitudinal clinical trials utilizing stem cells derived from adipose tissue. Early studies examining the safety of intravenous injection of AD-MSCs reported no adverse side effects, including no observed tumorigenicity.…”
Section: Ad-mscsmentioning
confidence: 99%
“…ADMSCs have a wide range of sources, and are easily acquired and cultured without ethical issues [25]. ADMSCs and BMSCs have similar properties and play important roles in promoting angiogenesis, wound healing, reducing inflammatory response and activating lymphocyte proliferation, and thus more and more clinical studies has applied ADMSCs transplantation to treating SCI.…”
Section: Adipose-derived Mesenchymal Stem Cells (Admscs)mentioning
confidence: 99%
“…ADMSCs and BMSCs have similar properties and play important roles in promoting angiogenesis, wound healing, reducing inflammatory response and activating lymphocyte proliferation, and thus more and more clinical studies has applied ADMSCs transplantation to treating SCI. ADMSCs accumulates in the injured spinal cord through vein grafting, then activate cytokines and accelerate the recovery of motor function and tissue repair in rats [25]. Hur et al [26] performed intrathecal autologous transplantation of ADMSCs in 14 patients with SCI, no serious adverse events were found during 8 months of follow-up, and some patients exhibited slight neurological improvement.…”
Section: Adipose-derived Mesenchymal Stem Cells (Admscs)mentioning
confidence: 99%